The demographics of Tolosa-Hunt syndrome in Qatar - Fateen Ata (12217764) (2021)
Background Tolosa Hunt syndrome (THS) is a rare disease that manifests mainly as painful unilateral ophthalmoplegia. It is caused by an inflammatory process of unknown aetiology within the cavernous sinus with a rare intracranial extension. The International Classification of Headache Disorders (ICHD)- 3 diagnostic criteria aids in its diagnosis. There is limited literature on its varied presentations, diagnosis, and management. Steroids are used in the treatment of THS with varied success. Methods We conducted a single-center-retrospective-study and included all patients admitted with a diagnosis of THS from January 2015 to December 2020. Descriptive and summary statistics were used to describe the study cohort's socio-demographic parameters. Results Among 31 THS patients (predominantly Asians (18) and Arabs (9)), visual disturbance was commonest presenting complaint. Third-nerve paralysis was seen in 70.9% cases. Magnetic-resonance-imaging (MRI) was abnormal in 64.5%. 93.5% patients received steroids, with a response-rate of 70.9% and a recurrence-rate of 9.7%. A previous history of THS and female gender were associated with recurrence (p-value 0.009 and 0.018). Recurrence was seen in 66.7% fully recovered and 33.3% partially recovered cases (p-value 0.04). Among the benign and inflammatory subtypes of THS, the ICHD-3 criteria were applicable in 85% of inflammatory THS. Conclusions THS is a rare disease with ethnic variation in presentation and response to treatment. In our cohort female gender and a previous history of THS were associated with recurrence. ICHD-3 diagnostic criteria had a higher validity in our patients compared to prior studies, especially among the inflammatory THS. Other Information Published in: eNeurologicalSci License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ensci.2021.100359